Influencing factors at the time of choice by a graduation and mode of teaching under the perception of students high school (Research, Society and Development, 2020)
The search for educational qualification becomes a competitive differential. Defining a degree by face-to-face or distance learning can be a differential in the student curriculum. This research has as study problem: what are the relevant factors for students of the 2nd and 3rd years of high school when considering opting for a degree? The main objective of the study is to identify the relevant factors in the decision on the degree to be chosen. The deductive, qualitative and quantitative approach was used. As methods of procedure the descriptive study and case study. The techniques of data collection were bibliographic research, documentary research and questionnaire. 318 responses were collected and from the tabulation of the data obtained it was identified that the quality of teaching is presented as the highest priority by students, followed by the market opportunities offered by the desired course and the quality of the faculty. The data also reveal that these students, mostly are between 15 and 17 years old, predominantly female with 54.43%. Regarding the face-to-face and distance learning modality, 80.20% of the respondents stated that they prefer to undertake higher education in an institution in person. It is concluded that despite the difficulties imposed by the Brazilian economy, most students still prefer to carry out higher education in institutions in person, anchored by factors involving the quality of teaching, quality of the faculty and opportunities in the labor market, in addition to In addition, a study made it possible to explain feelings and desires about the choices that involve graduation.